Application running method and device and electronic equipment - WANG XINGCAN (2020)
The invention discloses an application running method and device and electronic equipment, and the method comprises the steps: starting a system setting function associated with a target application corresponding to a target object under the condition that a first input to the target object is received, wherein the first input is used for starting the target application; and executing the system setting function in the process of running the target application in the foreground. According to the embodiment of the invention, user operation can be simplified. 本申请公开了一种应用运行方法、装置及电子设备，该方法包括：在接收到对目标对象的第一输入的情况下，启动与所述目标对象对应的目标应用所关联的系统设置功能；其中，所述第一输入用于启动所述目标应用；在前台运行所述目标应用的过程中，执行所述系统设置功能。本申请实施例可以简化用户的操作。